Philosophy of Education: The Nature of Students - Evi Nur Latipah; Maspuroh; Lisda Aulia Apriani; Muhammad Hamdani; Nadia Nur Kamila (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The nature of students is a crucial concept in education, as they are the primary subjects in the learning process. A deep understanding of the nature of students can help educators design effective learning strategies tailored to individual needs. This article aims to explore the nature of students from psychological, social, and cultural perspectives, as well as its implications for developing their potential and achieving educational goals. Students are viewed as individuals with unique characteristics, needs, and potential, so learning approaches must be holistic and inclusive. This research uses a literature review method to analyze various theories and perspectives on students. The results indicate that a comprehensive understanding of the nature of students can support the creation of a conducive learning environment and improve the quality of learning outcomes.